Pengaruh Keterlibatan Pengguna, Kemampuan Teknik Personal Dan Dukungan Top Manajemen Terhadap Kinerja Sistem Informasi Akuntansi - Yulia Wijayanti; Cris Kuntadi; Rachmat Pramukty (Jurnal Sistem Informasi dan Ilmu Komputer, 2023)
In research or scientific articles, previous or relevant research is very important because it helps strengthen theories and phenomena of the relationship or influence between variables. In the literature research on accounting information systems, this article analyzes user involvement, personal technical skills, and top management support. These factors affect the accounting information system. Building a hypothesis of influence between variables is the aim of this paper. The results of this literature research are as follows: 1) User Involvement influences the Accounting Information System; 2) Personal Technical Ability influences the Accounting Information System; and 3) Top Management Support.